High-intensity interval training and athletic performance in Taekwondo athletes - Monks, L.; Seo, M.-W.; Kim, H.-B.; Jung, H. C.; Song, J. K. (The Journal of Sports Medicine and Physical Fitness, 2017)
Background: The purpose of this study was to determine the effects of high intensity interval training (HIIT) on athletic performance in Taekwondo athletes. Methods: Thirty-three male and female collegiate Taekwondo athletes were randomly divided into a HIIT group (N=16) or a high intensity continuous running (HICR) group (N=17). The HIIT group undertook training of high intensity sprints interspersed with active rest periods whilst the HICR group participated in high intensity running for a continuous period. Both groups completed 11 sessions over 4 weeks. Physique, body composition, Wingate anaerobic test and VO2max test were measured. The vertical jump test, agility T-test and sit-ups were used to assess physical fitness. Repeated measures ANCOVAs with sex as a covariate were applied and significant level was set at 0.05. Results: Following 11 sessions of training, significant improvements in anaerobic peak power (P<.05), relative peak power (P<.05), and mean power (P<.05) were observed only in HIIT group compared to HICR group. A greater improvement of aerobic capacity was observed in HIIT group (8.8%) compared to the HICR group (1.7%). In relation to physical fitness, the HIIT group improved in the vertical jump while the HICR group did not change. Both the HIIT and HICR groups showed greater improvements in T-test and sit-ups during the intervention period. Conclusions: This study shows the effectiveness of eleven sessions of HIIT in producing significant improvements in anaerobic capacity relevant to successful Taekwondo competition performance in collegiate Taekwondo athletes. This could inform the future planning of Taekwondo athletes' pre-competition training, specifically the influence of training intensity on anaerobic capacity.